Perceptions of Fear, Likelihood of Victimization, and Confidence About Dangerous Situations Among University Women in Poland - Lickiewicz, Jakub (Journal of interpersonal violence, 2021)
Polish women have not been studied in regard to fear, likelihood, or confidence about dangerous situations, nor has there been an instrument to measure those perceptions. The purpose of the study was fourfold: first, to present the Polish translation and validation of the Perception of Dangerous Situations Scale (PDSS-P) and second, to assess Polish women’s perceived fear, likelihood, and confidence about dangerous situations using the PDSS-P (41 items). The third purpose was to determine to what degree the General Self-Efficacy Scale (GSES) and/or the Hope for Success Scale (KNS) correlated with any of the three subscales of the PDSS-P. The fourth purpose was to determine the congruence of the PDSS-P to the original PDSS. Two other tools (GSES and KNS) were administered to determine concurrent validity with the PDSS. A sample of 208 women aged 19 to 27 years (M = 21.04, SD = 1.88) participated in the study. Five factors were determined for each subscale, similar to the original version of the PDSS. Women reported they were more afraid of being raped by a stranger than being murdered. Their estimation of the likelihood of some serious events occurring was not congruent with statistical realities. The women thought the least likely events to happen to them in the next year would be being raped or beaten by someone they know, or being held prisoner by someone who wanted to murder them. Confidence to manage dangerous situations was low in cases of being raped by strangers or known people, being kidnapped, or being attacked. The GSES and KNS provided useful information, in that they did not measure the same constructs as the PDSS-P.